SMARANDACHE ANTI ZERO DIVISORS - Rebin M. Hassan; Suham H. Awla (Science Journal of University of Zakho)
In this paper, we study and discuss the concept of Smarandache anti zero divisor (SAZD) element of the ring  and the group ring , where  is a cyclic group of order  generated by . Moreover, we introduce and discuss the concept of SAZD ideal of the ring . Some results related to the given concepts are proved in detail. Accordingly, a Computer Algebra System (GAP) is used to verify the results of this study